2018
DOI: 10.1038/s41467-018-07316-5
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism induced by Bmp signaling is essential for murine skeletal development

Abstract: Much of the mammalian skeleton originates from a cartilage template eventually replaced by bone via endochondral ossification. Despite much knowledge about growth factors and nuclear proteins in skeletal development, little is understood about the role of metabolic regulation. Here we report that genetic deletion of the glucose transporter Glut1 (Slc2a1), either before or after the onset of chondrogenesis in the limb, severely impairs chondrocyte proliferation and hypertrophy, resulting in dramatic shortening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 51 publications
2
104
0
Order By: Relevance
“…This may be explained by the short duration of Glut1 deficiency combined with a relatively low basal rate of bone formation, or due to potential compensatory mechanisms. Previously, deletion of Glut1 with Prx1-Cre had little impact on osteoblast differentiation in the mouse embryo even though the mineralizing activity appeared to be partially impaired (42). In vitro experiments in the current study showed that Glut1 deletion markedly reduced glucose metabolism by osteoblast lineage cells, thus arguing against functional compensation by the other glucose transporters.…”
Section: Discussionmentioning
confidence: 45%
“…This may be explained by the short duration of Glut1 deficiency combined with a relatively low basal rate of bone formation, or due to potential compensatory mechanisms. Previously, deletion of Glut1 with Prx1-Cre had little impact on osteoblast differentiation in the mouse embryo even though the mineralizing activity appeared to be partially impaired (42). In vitro experiments in the current study showed that Glut1 deletion markedly reduced glucose metabolism by osteoblast lineage cells, thus arguing against functional compensation by the other glucose transporters.…”
Section: Discussionmentioning
confidence: 45%
“…One interpretation of these results is that glucose metabolism is affected in the resident trabecular bone cells: the osteoblasts and osteoclasts. Although the effect of lactate accumulation in these cells has not been studied in detail, it is known that they rely on glucose uptake for cell differentiation and bone formation . In fact, recent studies showed that osteoblasts preferentially use glycolysis for ATP production, even under aerobic conditions, mimicking the Warburg effect .…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of lactate accumulation in these cells has not been studied in detail, it is known that they rely on glucose uptake for cell differentiation and bone formation. (50,72) In fact, recent studies showed that osteoblasts preferentially use glycolysis for ATP production, even under aerobic conditions, mimicking the Warburg effect. (73,74) It is therefore possible that loss of MCT4 may directly affect the metabolic profile of osteoblasts and interfere with proper trabecular bone formation and turnover in the vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…The compensatory upregulation of Tret1-1 transcription is independent of insulin/adipokinetic hormone signaling, but instead depends on TGF-β signaling. This regulatory mechanism that allows sparing the brain from the effects of malnutrition is likely conserved in mammals, since mammalian Glut1 is also upregulated in the BBB upon hypoglycemia and has been shown to be induced by TGF-β signaling in other tissues (Boado and Pardridge, 1993;Kumagai et al, 1995;Simpson et al, 1999;Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%